Development of fusarium wilt resistant and high yielding watermelon (Citrullus lanatus L.) variety through marker- assisted backcross breeding - Kolapo, Olalekan Kazeem (2019)
One of the major production limiting diseases of watermelon (Citrullus lanatus L.) is Fusarium wilt (FW) caused by Fusarium oxysporum f. sp. niveum (FON). The use of disease-free cultivars is the preferred method of controlling the disease in a sustainable way. Watermelon is a major crop in Malaysia and the country spends about RM 10 million annually for the importation of its seeds to support local production. There is therefore the need to save this huge amount by breeding for local varieties that will be high yielding and Fusarium wilt resistant. In this study, the Fusarium wilt resistant inbred line CS-19 and susceptible inbred line BL-14 were crossed to generate the F1 population. The subsequent two backcrosses and selfing led to the transfer of the resistance gene (fo-1) into the susceptible inbred line BL-14 using marker-assisted backcrossing (MABC) and the subsequent development of Fusarium wilt resistant lines that still retain the desirable qualities in BL-14. Eleven microsatellite markers linked to the Fusarium wilt resistance gene were selected and two of the markers, BVWS02309 and BVWS01133 located on chromosomes 1 and 9 respectively were used for the confirmation of Fusarium wilt resistant gene in F1,BC1F1, BC2F1 and BC2F2 generations. From the 380 microsatellites markers screened, 78 were found polymorphic between the parents and used for recurrent parent genome (RPG) recovery in each backcross population. From the inheritance test conducted in BC2F1 and BC2F2 generations, the recurrent parent BL-14 scored 4.5 of the 0-5 scale, and this confirmed its susceptibility to the Fusarium wilt disease. In the BC2F1 generation, 72 of the 150 plants showed resistance while 78 plants showed susceptibility when inoculated with the virulent Fusarium oxysporumniveum isolate. Chi-square test (χ2) showed that the observed frequencies in the BC2F1 population fitted into the single gene model. The goodness of fit (p=0.46) to the expected test segregation ratio (1:1) indicated that the resistance is controlled by a single dominant gene. The plants resistant to the Fusarium oxysporum niveum isolate from BC2F1 population showed good fit with the two markers BVWS02309 (χ2= 0.24; p= 0.6892) and BVWS01133 (χ2= 0.11; p= 0.8065), with expected segregation ratio (1:1) for single gene model. These two markers were found suitable for marker-assisted selection of fo-1 gene against Fusarium wilt disease. The BC2F2 population phenotypically segregated into 3:1 ratio (resistant: susceptible). The genotypic segregation of the BC2F2 population using the two markers was in the ratio 1:2:1. This is a confirmation of the fact that resistance to Fusarium wilt disease in CS-19 is under the control of a single dominant gene. The RPG recovery analysis for the best improved lines ranged from 74.7 to 94.4% in BC1F1, 86.8 to 96.8% in BC2F1 and 95.1 to 96.9% in BC2F2 generations. The 96.14% average proportion of the recurrent parent genome in selected improved lines showed the close phenotypic resemblance to the recurrent parent BL-14. Ten homozygous lines carrying Fusarium wilt resistance gene with similar genome background to BL-14 were selected as the developed improved Fusarium wilt resistant breeding lines. The agro-morphological traits showed that there was no significant difference between the recurrent parent BL-14 and Fusarium wilt resistant improved lines developed. In conclusion, this study confirmed that Fusarium wilt resistance inbred line CS-19 is under the control of a single dominant gene and it is linked with SSR markers BVWS02309 and BVWS01133. This finding is recommended for use in marker-assisted selection for further development of Fusarium wilt resistant varieties with the newly developed resistant lines serving as source of resistance.